Retreatment with progestin for recurrence after complete response with fertility-sparing treatment in patients with endometrial cancer. Issue 8 (24th June 2022) - Lee, A Jin; Shim, Seung-Hyuk; Kim, Nae Ry; Yang, Eun Jung; So, Kyeong A; Lee, Sun Joo; Lee, Ji Young; Kim, Tae Jin; Kang, Soon-Beom
Abstract : Objective: To assess the outcomes of retreatment using progestin for recurrence after a complete response with fertility-sparing treatment in patients with early endometrial cancer. Methods: We retrospectively reviewed the data of patients with presumed stage IA, grade 1 endometrioid endometrial cancer who developed intra-uterine recurrence after a complete response with fertility-sparing treatment using progestin. Oncological and pregnancy outcomes were analyzed after repeated fertility-sparing treatment. Logistic and Cox regression analyses were performed to analyze the prognostic factors associated with a complete response with secondary fertility-sparing treatment and recurrence-free survival after secondary fertility-sparing treatment, respectively. Results: Fifty patients with a median age of 31 years (range 23–40) underwent secondary fertility-sparing treatment. With a median secondary progestin treatment duration of 9 months (range 3–55), the complete response rate was 78% (39/50) and no patients had extra-uterine spread of disease. Among the 26 (67%) patients who attempted to conceive after complete response, 10 became pregnant (3 spontaneous abortions, 7 live births). Eighteen (46.1%) patients had a second recurrence, with a median recurrence-free survival after secondary fertility-sparing treatment of 14 months (range 3–36); 15 patients received tertiary fertility-sparing treatment and nine (60%) achieved a complete response. Polycystic ovary on ultrasound (OR 5.82, 95% CI 1.1 to 30.6, p=0.037) was associated with an increased complete response rate with secondary fertility-sparing treatment. Multivariable analysis revealed that recurrence-free survival after initial hormonal treatment >6 months (HR 0.11, 95% CI 0.02 to 0.51, p=0.005) and pregnancy after secondary fertility-sparing treatment (HR 0.27, 95% CI 0.08 to 0.98; p=0.047) were significantly associated with longer recurrence-free survival after secondary fertility-sparing treatment. Conclusions: Repeated progestin treatment was associated with a 78% response rate and it was safe in patients with intra-uterine recurrent endometrial cancer. Thus, it might help preserve fertility after first and second recurrences.